Assessing the benefits and safety profile of incorporating poly ADP-ribose polymerase (PARP) inhibitors in the treatment of advanced lung cancer: a thorough systematic review and meta-analysis - Tang, Min; Wang, Yue; Li, Pulin; Han, Rui; Wang, Ran (Frontiers in Pharmacology, 2024)
Background: Poly (ADP-Ribose) Polymerase (PARP) inhibitors represent a novel class of drugs that hinder DNA repair mechanisms in tumor cells, leading to cell death. This systematic review aims to evaluate the effectiveness, safety, and potential adverse effects of PARP inhibitors (PARPi) in the management of patients with advanced lung cancer.We conducted a comprehensive search for relevant studies in PubMed, Embase, Cochrane, and ClinicalTrials.gov. We extracted primary and secondary outcome measures, including progression-free survival (PFS), overall survival (OS), and adverse events (AEs), from the identified literature for subsequent meta-analysis and systematic review.Results: This study encompassed twelve randomized controlled trials, involving 3132 patients with advanced lung cancer. In comparison to non-PARPi treatments, the administration of PARP inhibitors significantly extended overall survival (hazard ratio (HR) = 0.90, 95% CI = 0.83-0.97, p = 0.006). However, the difference in progressionfree survival did not reach statistical significance.In summary, therapies incorporating PARP inhibitors provide a degree of benefit by extending overall survival in patients with advanced lung cancer.Nonetheless, further trials are necessary to furnish additional evidence regarding the efficacy and safety of PARP inhibitors in the treatment of lung cancer.